Isolation and characterization of major diterpenes from C. canephora roasted coffee oil. Issue 14 (15th August 2016) - Guercia, Elena; Berti, Federico; Navarini, Luciano; Demitri, Nicola; Forzato, Cristina
Graphical abstract: Abstract: A simple laboratory procedure for the isolation of pure cafestol and 16- O -methylcafestol together with β-sitosterol from coffee is disclosed. Cafestol and 16- O -methylcafestol have been exhaustively characterized through 1D and 2D 1 H, 13 C NMR, CD and X-ray diffraction. For the first time, the molecular structure of cafestol is reported and the assignment of the absolute configuration is unequivocally given by exploiting anomalous scattering of a brominated derivative. Abstract : Cafestol: C20 H28 O3 Ee = n.d. [ α ]D 20  = −119 ( c 0.06, CH3 OH) Source of chirality: natural source Absolute configuration: (5 S, 8 S, 9 R, 10 S, 13 R, 16 R ) Abstract : 16- O -Methylcafestol: C21 H30 O3 Ee = n.d. [ α ]D 20  = −102 ( c 0.13, CH3 OH) Source of chirality: natural source Absolute configuration: (5 S, 8 S, 9 R, 10 S, 13 R, 16 R ) Abstract : p -Bromobenzoyl ester of cafestol: C27 H31 BrO4 Ee = n.d. [ α ]D 20  = −84.0 ( c 0.13, CHCl3 ) Source of chirality: natural source Absolute configuration: (5 S, 8 S, 9 R, 10 S, 13 R, 16 R )